High-Energy Emulsified Clove Essential Oil Nanoemulsion as a Natural Herbicidal Product: Germination Suppression and Seed Structure Alteration in Echinochloa crus-galli - Potjana Sikhao; Naphat Somala; Nutcha Manichart; Jantra Dimak; Thanatsan Poonpaiboonpipat; Kaori Yoneyama; Montinee Teerarak; Chamroon Laosinwattana; Nawasit Chotsaeng (Plants, 2026)
germination and seedling growth, and additionally, inhibited seed imbibition and α-amylase activity. Micro-morphological and ultrastructural analysis was observed using a scanning electron microscope and an energy dispersive X-ray spectrometer (SEM-EDS). SEM-EDS micrographs of the treated seeds showed that the seed structure was damaged, especially the endosperm, leading to the inhibition of seed germination.
Keywords: Allelopathy and phytotoxic interactions; Polymer-Based Agricultural Enhancements; Seed Germination and Physiology